دور الحوكمة المؤسسية كآلية فعالة لمكافحة الفساد الإداري والمالي في المؤسسات العامة دراسة وصفية تحليلية للحالة الليبية (Comprehensive Journal of Science, 2026)
This study examines the role of corporate governance as an effective tool for combating administrative and financial corruption in Libyan public institutions, in light of global economic challenges and the increasing demands for transparency and accountability. The study aims to assess the effectiveness of implementing governance principles within institutions, including financial disclosure, fairness, internal control, and accountability, and to analyze the relationship between these principles and the reduction of administrative and financial irregularities. The results showed that 70% of participants affirmed their institutions' commitment to transparency, and 65% indicated the application of the principle of accountability. However, some negative practices, such as favoritism and weak oversight, were observed in percentages ranging from 40% to 55%. The study also demonstrated that implementing governance principles contributes to enhancing institutional integrity, building trust within institutions, and improving their performance. It emphasized the need to strengthen internal participation and develop audit and oversight programs to minimize opportunities for corruption. The study recommends focusing on developing transparency and accountability mechanisms, promoting fairness and equality, strengthening internal controls, and regularly monitoring policy implementation to ensure effective governance and achieve sustainable development.
Keywords: Governance - Administrative and Financial Corruption - Corporate Oversight - Transparency and Accountability - Libyan Public Institutions